(untitled) (Eurasian Journal of Ecology, 2022)
Unique genetic resources of plant biodiversity are concentrated in Kazakhstan. Economically important species make a significant contribution to the structure of the Earth in comparison with taxa with insignificant or unknown economic use, many economically valuable species of Kazakhstan are of global importance. The purpose of this work is to identify economically valuable species of Northern Kyzylkum within the Republic of Kazakhstan. Objects and methods of research: To collect and identify species, classical botanical, route-reconnaissance; ecological-systematic; ecological-geographical methods were used. The main groups of useful plants of economically valuable flora species of Northern Kyzylkum were identified: woody, food, medicinal, fodder, decorative, technical species. During the research, it was revealed that 310 economically valuable species belonging to 62 families and 196 genera are found in Northern Kyzylkum within the Republic of Kazakhstan. According to the results of the classification, the dominant families are determined: Poaceae Barnhart has 34 genera, 58 species; Asteraceae Dumortier – 24 genera, 46 species; Chenopodiaceae Vent. – 19 genera, 30 species; Fabaceae Juss. – 11 genera, 23 species. The study analyzed 200 types of medicinal, 100 types of fodder, 22 types of decorative, 11 types of sand fixers, 9 types used for fuel according to significant economic valuable characteristics. According to the classification of economically valuable species by life forms, tree forms were identified in 6 species: Salix alba L., Populus diversifolia Schrenk, P. pruinosa Schrenk, Acer negundo L., Elaeagnus angustifolia L., Haloxylon persicum Bunge ex Boiss., 44 shrubs and semi-shrubs, 155 perennials, 105 biennial and annual plants. Key words: economically-valuable species, Northern Kyzylkum, fodder, medicinal, useful, decorative.